The History of the Revival of Madrasahs as Islamic Educational Institutions in Madura - Moh. Hariri; Maimun; Muhammad Ihsan; Mohammad Suhud (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article discusses the historical development of madrasas in Madura, where Islamic education has a long history that began during the time of the Prophet Muhammad (peace be upon him) with teaching methods in homes and mosques. Over time, Islamic education has undergone transformation, especially with the emergence of madrasas as formal institutions that integrate religious knowledge and general knowledge. In Madura, Islamic boarding schools are the oldest Islamic educational institutions and play a vital role in maintaining Islamic values, as well as being the beginning of the emergence of madrasas in Madura. With the influence of modernization, madrasas emerged as a form of renewal of Islamic education. This study discusses the rise of madrasas in Madura, their important role in shaping the character and religious identity of the community, as well as the challenges and opportunities faced. Madrasas in Madura have successfully combined traditional values with the demands of modernity, while also becoming agents of social change that maintain harmony between the two. Despite facing challenges such as limited facilities and teacher quality, madrasas in Madura continue to play a vital role in maintaining the balance between religious education and general knowledge, as well as in strengthening the cultural and religious identity of the Madurese community. This study uses a literature review method by examining articles related to this research.